2003
DOI: 10.1080/02813430310002995
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of the effectiveness of feedback in improving test ordering in general practice

Abstract: Feedback did not have an influence on test ordering by general practitioners in this study. More intensive strategies may be required to change the use of laboratory tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 1 publication
1
42
0
Order By: Relevance
“…Audit and feedback have often been used and showed mostly a modest effect in terms of influencing test ordering or prescribing. The effect of audit and feedback on adherence to desired practice ranged from -10% to +68% (median +16%) [ 8 - 12 ]. In other studies, the introduction of a problem-based test ordering form proved to be a promising tool to improve test ordering [ 7 , 13 - 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Audit and feedback have often been used and showed mostly a modest effect in terms of influencing test ordering or prescribing. The effect of audit and feedback on adherence to desired practice ranged from -10% to +68% (median +16%) [ 8 - 12 ]. In other studies, the introduction of a problem-based test ordering form proved to be a promising tool to improve test ordering [ 7 , 13 - 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…22 Not all previous studies have been positive; Baker et al attributed failure to the short duration of feedback. 23 We believe that our strategy combining A&F, an incentive mechanism and education was benefi cial. A previous study has shown that a multiple strategy approach boosts the effect of A&F. 24 The infl uence of positive feedback (incentive) serves as another major contributing factor in the acceptance and success of A&F intervention in the current study.…”
Section: Mrd 3 Months After the Interventionmentioning
confidence: 92%
“…Baker believed that A&F of limited duration led to failure. 35 We believe that our A&F intervention was successful as we designed a behaviour-based intervention approach based on contributing factors identifi ed in our pilot study of clinicians' viewpoints.…”
Section: Discussionmentioning
confidence: 99%